DEVELOPING A MODULE OF COACHING THE CHARACTER DISCIPLINE THROUGH SCOUT EXTRACURRICULAR - Messi Messi; Muhammad Kristiawan; Yasir Arafat (Sriwijaya University Learning and Education International Conference, 2018)
This research starts from the results of a preliminary study that children unable to control himself well because at their age control of emotions is very labile. The objective of the research is to develop a module of coaching character discipline of students through Scouts’ extracurricular which valid, practical, and effective. The methods used in this research is the Research and Development with the ADDIE model. The subject in this study is SMK Negeri 3 Palembang. The data were collected by interview, observation, documentation and tests. The results showed that students could apply the character discipline through extracurricular Scouts, the conclusion that in this module was successfully developed and declared valid, practical and effective.